2015
DOI: 10.1007/s12640-015-9565-5
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Antibody and Botulinum Toxin Therapy: A Systematic Review and Meta-analysis

Abstract: The formation of neutralizing antibodies (NAbs) directed specifically against the active neurotoxin part of the botulinum neurotoxin (BoNT) complex is often cited as a major cause of secondary non-responsiveness (SnR) to treatment. This systematic and meta-analytic review evaluates the frequency of NAbs among patients treated with BoNT therapy for any clinical indication. A comprehensive database search strategy was designed to retrieve relevant clinical data from the published literature up to April 2013. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 31 publications
5
85
1
10
Order By: Relevance
“…25 Some discrepancy between the identification of neutralizing antibodies and secondary nonresponse has been described previously. 29 No lasting immunogenicity was recorded with increasing incobotulinumtoxinA dose across the entire study period (up to 48 weeks) and higher than labeled doses were administered in both cycles 2 and 3. Further studies are required to investigate the effect of long-term treatment with high doses of incobotulinumtoxinA on the development of immunogenicity.…”
Section: Discussionmentioning
confidence: 94%
“…25 Some discrepancy between the identification of neutralizing antibodies and secondary nonresponse has been described previously. 29 No lasting immunogenicity was recorded with increasing incobotulinumtoxinA dose across the entire study period (up to 48 weeks) and higher than labeled doses were administered in both cycles 2 and 3. Further studies are required to investigate the effect of long-term treatment with high doses of incobotulinumtoxinA on the development of immunogenicity.…”
Section: Discussionmentioning
confidence: 94%
“…These patients often are thought to have acquired antibody-mediated resistance that blocks the BoNT protein from its normal action [1922]. This mechanism for non-response was studied extensively with early BoNT preparations, but more recent studies have suggested that antibody formation is uncommon with the currently available highly purified BoNT preparations.…”
Section: Discussionmentioning
confidence: 99%
“…When formal tests of resistance are indicated, there are two options. The first option involves commercially available tests for antibodies to BoNT, although these have fallen out of favor because of poor clinical correlations [1517, 20, 22, 38]. The preferred option involves performing a functional test for muscle weakness, such as injection of a small dose of BoNT into the frontalis, corrugator, or extensor digitorum brevis [19].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary non-response is partially explained by the formation of neutralizing antibodies, though it is worth noting that there are cases of secondary non-responders without positive antibody titers (Hanna 1998;Lange 2009) as well as cases with positive titers but with an adequate sensitivity to Bt (Brin 2008;). An estimated 4-20% of patients develop neutralizing antibodies to the toxin (Brashear 2008;Fabbri 2015), and if secondary non-responsiveness occurs, it is partially related to the protein load, with higher protein load per dose generating higher antibody titers (Benecke 2012;Frevert 2010). …”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%